2017
DOI: 10.1186/s13756-017-0172-5
|View full text |Cite
|
Sign up to set email alerts
|

Prospective surveillance of healthcare associated infections in a Cambodian pediatric hospital

Abstract: BackgroundHealthcare associated infections (HAI) are the most common preventable adverse events following admission to healthcare facilities. Data from low-income countries are scarce. We sought to prospectively define HAI incidence at Angkor Hospital for Children (AHC), a Cambodian pediatric referral hospital.MethodsProspective HAI surveillance was introduced for medical admissions to AHC. Cases were identified on daily ward rounds and confirmed using locally adapted Centers for Disease Control and Prevention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…From 2011–2012 onward, the proportion of resistant hospital-acquired K. pneumoniae isolates declined. This drop may be linked to maturation of a hospitalwide infection-control program implemented in 2010 ( 20 ) and enforced by prospective hospital-acquired infection surveillance from 2015 onward ( 21 ) or to the clinical microbiology service operating since 2012 with a strong focus on antimicrobial drug stewardship. Indeed, a recent study of prescribing practices at this hospital found 84%–89% of antimicrobial drug prescriptions were appropriate ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…From 2011–2012 onward, the proportion of resistant hospital-acquired K. pneumoniae isolates declined. This drop may be linked to maturation of a hospitalwide infection-control program implemented in 2010 ( 20 ) and enforced by prospective hospital-acquired infection surveillance from 2015 onward ( 21 ) or to the clinical microbiology service operating since 2012 with a strong focus on antimicrobial drug stewardship. Indeed, a recent study of prescribing practices at this hospital found 84%–89% of antimicrobial drug prescriptions were appropriate ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although multi-center studies reporting HAIs in other countries were not published, a single-center study in an ICU reported a high device associated HAI incidence rate of 27.3 per 1000 patient-days in Nepal (68). In Pakistan, a single pediatric ICU study reported a device associated HAI incidence rate of 6.3 per 1000 patient-days (69), whereas in Cambodia, the device associated HAI incidence rate in one pediatric ICU was reported as 4.6 per 1000 patientdays (70).…”
Section: Bacterial Disease Burden In Hospital-acquired Infectionsmentioning
confidence: 99%
“…We did not identify a systematic review that included data from multiple countries in the South Asia or South East Asia region reporting causes of hospitalacquired bacteremia. The organisms causing hospital-onset bacteremia (defined as blood cultures obtained after 48 hours of admission to a hospital) in eight countries determined using studies published between 2010 and 2018 (42,50,55,56,62,70,(73)(74)(75) (Supplementary Table S2) are listed in Table 2. We identified very few or no studies from Bangladesh, Pakistan, and Laos that determined the causes of hospital-acquired bacteremia, indicating the need for more comprehensive studies in these areas.…”
Section: Etiology Of Hospital-acquired Bacteremiamentioning
confidence: 99%
“…As per WHO guidelines, infection prevention and control (IPC) is a practical, evidence-based approach to prevent patients and health workers from being harmed by avoidable infections. Statistics revealed that maintaining effective IPC resulted in a O30% reduction in healthcare-associated infections (HAIs) (14). Hence, considering the global emergency of CoVID-19 infections, preventive care is the only option left to restrict its spreadability.…”
Section: Introductionmentioning
confidence: 99%